2016
DOI: 10.1021/acs.jpcb.6b10556
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Aqueous Trehalose Solution by Neutron Diffraction and Structural Modeling

Abstract: The molecular structure of an aqueous solution of the disaccharide trehalose (CHO) has been studied by neutron diffraction and empirical potential structure refinement modeling. Six different isotope compositions with 33 wt % trehalose (corresponding to 38 water molecules per trehalose molecule) were measured to ensure that water-water, trehalose-water, and trehalose-trehalose correlations were accurately determined. In fact, this is the first neutron diffraction study of an aqueous trehalose solution in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 49 publications
11
32
0
Order By: Relevance
“…Nonetheless, quantitative results are valuable to obtain to allow us to compare our findings to previous works, such as those in refs 1, 33, 34, and 41. Within the limits of the error bars, our hydration numbers of trehalose (Table S2) are consistent with these previous studies, 1,33,34,41 although our interpretation of the experimental results and models differs somewhat from those studies as further discussed below.…”
Section: ■ Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, quantitative results are valuable to obtain to allow us to compare our findings to previous works, such as those in refs 1, 33, 34, and 41. Within the limits of the error bars, our hydration numbers of trehalose (Table S2) are consistent with these previous studies, 1,33,34,41 although our interpretation of the experimental results and models differs somewhat from those studies as further discussed below.…”
Section: ■ Resultssupporting
confidence: 91%
“…Although the fits capture most features of the experimentally obtained diffraction data and are in relatively good agreement (compared to e.g. previous mentioned studies on trehalose 1,33,34,41 ), there are still several discrepancies with the experimental data. These discrepancies are definitely larger than the experimentally measured differences between sucrose and trehalose.…”
Section: ■ Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…[22][23][24][25] It has also been shown that trehalose exhibits a stronger coupling of its dynamics to the dynamics of the proteins, compared to other disaccharides. 26,27 In order to study molecular dynamics of proteins and disaccharides in the presence of water, many different methods are commonly used, such as molecular dynamics simulations, 13,18,25 neutron scattering techniques, 19,22,[28][29][30][31][32][33][34][35][36][37][38][39] Raman-spectroscopy 17,[40][41][42][43] and many others. One particular method which has often been used, particularly for the purpose of studying disaccharides [44][45][46][47][48] and proteins, is dielectric spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Relating the molecular structure of trehalose to its conformations is extremely challenging. NMR, 6,7 X-ray 1 and neutron scattering 8,9 measurements have been performed to probe the trehalose-water interactions, in particular, which were complemented by numerical simulations. 1,5,10,11 Beyond that, the conformations and assembly motifs of saccharides in environments of reduced symmetry, e.g.…”
Section: Introductionmentioning
confidence: 99%